A bidirectional DC-DC converter with high voltage conversion ratio and zero ripple current for battery energy storage system - Wang, Zhishuang (2022)
In this article, a novel bidirectional dc-dc converter (BDC) consisting of an active switched-inductor (A-SL) cell, a zero current ripple cell and an auxiliary capacitor cell is proposed for the battery energy storage system. The proposed BDC integrates with the advantages of high voltage conversion ratio, low power switch voltage stresses, zero ripple current on the low voltage side (LVS), and constant potential difference between the grounds of LVS and high voltage side. Thanks to the use of synchronous rectification technology, the efficiency of the proposed BDC is increased. The operating principles, the characteristics analysis and the parameter design of the proposed BDC are given. In addition, to show the merits of the proposed BDC, a comparison study involves the proposed converter and other BDCs is demonstrated. Finally, some experimental results obtained using a 1000 W prototype are presented to valid the effectiveness of the proposed BDC. 96.43% and 96.67% maximum conversion efficiencies can be achieved in the step-up and step-down modes, respectively.